Dams, development, displacement and tribals - Verghese, B.G. (2006)
India's explosive demographic growth and galloping urbanisation are rapidly increasing the demand for both water and electrical power. Large hydro-electrical projects are hence necessary even though they cause extensive social and ecological problems which must be comprehensively addressed by the state. However, it should be kept in mind that a lack of development and the want of water and employment cause massive human displacement, social strife and injustice, also resulting in irreversible environmental degradation. - Reproduced.
Keywords: Tribes; Refugees; Dams